Effect of variable amplitude block loading on fatigue crack growth - Neto, D. M. (2022)
The objective is to study the effect of load blocks on fatigue crack propagation. To carry out this study, the finite element program DD3IMP will be used, with the fatigue crack propagation being controlled by the value of the plastic deformation at the end of the crack. The material used was the Ti6Al4V alloy obtained by the selective laser fusion manufacturing process. Regarding the studied load patterns, two types of High-Low load blocks and two types of Low-High load blocks were studied. A plane stress state was always considered and the influence of the contact between the crack flanks on the predicted FCG rate is highlighted by removing numerically the contact conditions. The transient behavior observed between loading blocks of different amplitude is strongly reduced or vanishes when the contact is neglected. For load blocks with high values of stress ratio, the predicted FCG rate in steady state regime is approximately the same considering or neglecting the contact of the crack flanks. On the other hand, for low values of stress ratio, the predicted FCG rate is lower when the contact of the crack flanks is considered, which is related with crack closure level.